Loss of Pancreatic β-cell Secretory Function During Disease Progression in Type 2 Diabetes Mellitus - A Small Cross-Sectional Study - George B. Kudolo (Pancreas, 2025)
Introduction: Overt type 2 diabetes mellitus (T2DM) is a chronic progressive disease which is produced by the collusion of three metabolic defects-increased hepatic glucose production, impaired pancreatic β-cell insulin secretion and decreased insulin action. The measurement of plasma glucose 2 hours post-ingestion of 75 g of glucose during the oral glucose tolerance test (OGTT) may be used to classify individuals as normal glucose tolerant (NGT), impaired glucose tolerant, T2DM and T2DM with pancre-atic β-cell failure.Objectives: This study was undertaken primarily to show the importance of assessing the pancreatic β-cell function especially during the care of the diabetic patient.Methods: A standard 75 g glucose tolerance test (OGTT) was administered to four groups of 8 subjects (4 male, 4 female). Blood was drawn every 15 minutes for 2 hours for the measurement of glucose, insulin and C-peptide and the measurement of the area under the curve (AUC(0→2)) over the 2-hour period.Results: American Diabetes Association (ADA) criteria were used to classify the subjects. The normal glucose tolerant (NGT), had 2 h glucose 111±11 mg/dL, those with impaired glucose tolerance (IGT) had 2 h glucose 160±13 mg/dL. The 2 h glucose for the T2DM group was 258±27 mg/dL and those for the T2DM-PE group was 260±42 mg/dL. The AUC(0→2) for NGT group were 254±40 mg/dL/h, 112±61 μU/mL/h and 10.2±4.6 ng/ml/h for glucose, insulin and C-peptide, respectively. The AUC(0→2)for the IGT group were 394±32 mg/dL/h, 160±48 μU/mL/h and 19.8±7.7 ng/ml/h for glucose, insulin and C-peptide, respec-tively. The AUC(0→2) for the T2DM group were 474±62 mg/dL/h, 194±40 μU/mL/h and 13.4±4.7 ng/mL/h for glucose and in-sulin, and C-peptide, respectively. The AUC(0→2) for the T2DM-PE group were 481±80 mg/dL/h, 51±29 μU/mL/h and 7.2±2.8 ng/mL/h for glucose, insulin and C-peptide, respectively. There was no significant difference between the diabetic groups with respect to the glucose AUC(0→2) but a significant difference existed in the insulin AUC(0→2), (p<0.0001) mirrored by the fasting plasma insulin levels (30±8 μU/mL vs 14+8 μU/mL, for T2DM and T2DM-PE, respectively, p<0.0005). Although there wasabout a 300% increase in fasting insulin between the IGT and T2DM groups, the corresponding fasting C-peptide levels wereonly about 15%. This is probably due to differences in hepatic and renal functions in those two groups, the processes that controlinsulin and C-peptide levels in the body.Conclusion: Although measurement of blood glucose appears adequate in the diagnosis of the diabetes, it seems that plasma insulin/C-peptide measurements could guide physicians in their choice of medications for the treatment of diabetic patients, especially when the pancreas begins to fail. To that end, larger studies are warranted to study the effects of hypoglycemic agents on hepatic insulin extraction and renal C-peptide excretion to ascertain the reliability of the plasma insulin and C-peptide levels.